The complex Ginzburg Landau model for an oscillatory convection in a rotating fluid - Manjula, S.H.; Kiran, Palle; Bhadauria, Beer Singh; Reddy, P. Raj (Zielona Góra: Uniwersytet Zielonogórski)
A weakly nonlinear thermal instability is investigated under rotation speed modulation. Using the perturbation analysis, a nonlinear physical model is simplified to determine the convective amplitude for oscillatory mode. A non-autonomous complex Ginzburg-Landau equation for the finite amplitude of convection is derived based on a small perturbed parameter. The effect of rotation is found either to stabilize or destabilize the system.
Keywords: convection; finite amplitude; nonlinear theory; rotation modulation; Nusselt number